The effect of red ginger extract as a feed additive of broiler quail - Muttaqin, Abdul Zainal; Abun, Abun; Sujana, Endang (Universitas Halu Oleo, 2023)
This study aims to evaluate the effect of dietary inclusion of red ginger extract (Zingiber officinale var. rubrum) on total coliform of intestinal bacteria, digestibility, and performance of broiler quail. A total of 100 unsexed broiler quail were randomly assigned into five groups of treatment with four replications (5 quail each). Dietary treatments applied were P0 = basal feed + 0 mg/kg red ginger extract ; P1 = basal feed + 500 mg/kg red ginger extract; P2 = basal feed + 750 mg/kg red ginger extract; P3 = basal feed + 1000 mg/kg red ginger extract and P4 = basal feed + 4000 mg/kg tetracycline. Experimental feed were given to quail after 2 to 6 weeks old. Data were analyzed to test of variance and followed by Duncan test. The results reveal that the supplemented of red ginger extract in the feed had a significant effect (P<0.05) on total coliform bacteria in the quail intestine and nutrient digestibility, but did not have a significant effect (P>0.05) on growth performance. In conclusion, red ginger extract has a positive effect on total coliform of intestinal bacteria and nutrient digestibility but has no significant effect on growth performance broiler quail.